(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Providing security and privacy in today’s digital era is very crucial. In order to ensure that the sensitive user data can only be accessed by a valid server, the user and server should agree on a common key in advance. To do so, in the last decade, a number of dynamic ID-based authenticated key agreement (DIDAKA) protocols have been proposed, which can guarantee subsequent secure communications of users and servers. Nevertheless, investigating the related works indicates that the existing DIDAKA schemes suffer from one or more security challenges. Quite recently, Xie et al. have presented an interesting anonymous DIDAKA protocol to cover the security weaknesses of previous schemes; nonetheless, we found that their scheme is susceptible to three attacks. Therefore, to remedy the security limitations, in this paper, we propose a security-enhanced anonymous DIDAKA protocol, which not only keeps the merits of Xie et al.’s scheme, but also offers better execution time compared to their proposed one. To demonstrate the security of the proposed scheme, we present both formal security proof and automatic formal verification of security and to show its efficiency, we present an extensive comparative performance analysis. In conclusion, the results are indicative of the priority of the proposed scheme.